Impact of land use types on soil microbial community structure and functional structure in Baihualing Village, China - Ruilong Huang; Wei Li; Shouming Qiu; Yuanli Long; Zhuanfei Zeng; Juan Tang; Qiuhan Huang (Global Ecology and Conservation)
Soil microorganisms play important ecological roles, and land-use practices have profoundly altered their composition, diversity and functions. However, most existing research has been conducted in areas with high levels of anthropogenic impacts. Microorganisms in these areas have adapted to long-term anthropogenic perturbations, leading to an underrepresentation of such impacts on microbial community structure and functions. Consequently, the true extent of these perturbations is often underestimated. Therefore, it is crucial to analyze the effects of land use practices on soil microbial communities in areas with low anthropogenic impacts. The Gaoligong Mountains, a boundary mountain range between China and Myanmar, are rich in biodiversity and have experienced low levels of anthropogenic disturbances. The present study focuses on the biodiversity-rich Gaoligong Mountains, aiming to explore how different land-use types affect the structure, diversity and function of soil microbial communities, and to identify the key soil environmental factors that drive these changes. Soil samples were collected from scrubland (SL), bird puddles (BP), coffee land (CL), orange land (OL), maize land (ML) and forestland (FL). High throughput sequencing was then used to determine the composition and diversity of soil microbial communities. The results revealed that bacterial diversity was significantly higher in scrubland (SL), bird puddles (BP), and forestland (FL) compared to the three agricultural lands, with bird puddles (BP) also exhibiting the highest fungal diversity. A further analysis showed that nitrate-nitrogen (NO3--N) was a key factor affecting microbial communities. C-cycle and N-cycle related functional groups are the dominant functional groups of the soil bacterial community, both of which are most abundant in scrubland (SL). The relative abundance of soil saprotrophic fungi was significantly higher in the three agricultural land use types compared to scrubland (SL). In conclusion, this study provides clear evidence of the impact of land uses on the elusive soil organisms in the Gaoligong Mountains, which are frequently overlooked yet increasingly threatened by anthropogenic disturbances.